KOMUNIKASI VERBAL BERBAHASA INDONESIA ANAK TUNAGANDA KELAS VII SMP SLBB SIDAKARYA, DENPASAR - Kesuma Dewi, Ni Ketut Ari (Humanis, 2014)
The aim of this research is to take part in providing an idea in Bahasa and linguistic improvement. Moreover, in order to able to compare the process of language acquisition between a regular kid and a kid with mentally as well as physically handicapped This research was using Psycholinguistic and S-R Skinner model theory. There are three forms of language that are able to be received by a kid with mentally as well as physically handicapped; phoneme, lexical, and grammatical. A language acquisition and learning is a process in order to improve their language competence and skill to support their continued survival. A resistivity in a system of language acquisition can be affected by some obstacles during the learning process. The result of this research is getting sounds of understanding for deaf mute need strength and positive knowledge and repeating of learning progress and in average of dear mute has disorder articulation such as aphesis, syncope.
Keywords: handicapped, form, acquisition